Exploring the Impact of Renewable Energy on Climate Change in the GCC Countries - Kasem, Amira; Alawin, Mohammad (International Journal of Energy Economics and Policy, 2019)
This study provides a theoretical framework for the role of renewable energy in mitigating the climate change in the Gulf Cooperation Council (GCC) countries. The abundancy of renewable resources and widely accessible technology are the key drivers for the renewable energy business in the GCC. However, lack of effective policies and regulations, along with subsidized fuel prices, are slowing down the implementation of renewable resource options. This study will illustrate the potential, the challenges, and the barriers of implementing renewable energy technologies in the GCC region. In addition, this research empirically examines the impact of Renewable Energy Sources (RSS) and other factors in the GCC countries in reducing the carbon dioxide emissions, using pooled OLS regression analysis with fixed effect specification. The results indicate that renewable energy consumption, GDP per capita, and electrical power consumption have a statistically significant impact on CO2 emissions. Keywords: Renewable Energy, Electrical Power, GCC Countries JEL Classifications: Q20, Q30, Q40 DOI: https://doi.org/10.32479/ijeep.8477